Polymorphism of Microsatellite Loci on Y Chromosome in Long-Tailed Macaque Populations in Bali Island, Indonesia - Wandia, I Nengah; Soma, I Gede; Putra, I Gusti Agung Arta (Veterinary Science and Medicine Journal; Vol 2 No 2 (2014), 2014)
The long tailed macaques inhabit throughout Bali Island, however, recently they have been fragmented into many smaller local populations. In spite of that, there are just few reports that describe the mode of fragmentation and the genetic structure of the population. This research aimed to explore the polymorphism of microsatellite loci on Y chromosome in long tailed macaque populations in Bali Island using three human microsatellite primers, namely DYS390, DYS391, and DYS393. A total of 99 blood samples were collected from male long tailed macaques originated from 8 populations (23 from Pulaki, 11 from Bedugul, 13 from Mekori, 8 from Sangeh, 6 from Uluwatu, 11 from Alas Kedaton, 11 from Ubud, and 16 from Bukit Gumang). Total DNA was extracted using QIAamp® Blood Mini Kit. The polymorphism of the microsatellite loci was detected using PCR technique, and allelic variations were separated through 7% poly acrylamide gel electrophoresis. The result of the research showed that DYS390 and DYS393 loci were monomorphic (each had only one allele). The DYS391 locus had two alleles, therefore, this locus was polymorphic. It could be suggested that DYS391 locus could be used to study genetic variation in male long tailed macaque population in Bali Island.
Keywords: long tailed macaques, polymorphism, microsatellite locus, Y chromosome, Bali Island